TINJAUAN ATAS PENGAKUAN PENDAPATAN RETRIBUSI PADA BADAN KEUANGAN DAERAH KOTA DEPOK - Pingkan Budi Wulansari, (2021)
Retribution is a levy paid for the use of services provided by the local government. Levies include revenues earned by local governments. The purpose of this Final Project Report is not only to fulfill the requirements for obtaining an associate degree but also to review the retribution income at the Depok City Regional Finance Agency whether it is in accordance with applicable government accounting regulations and standards. This Final Project report discusses the recognition, measurement, recording, presentation and disclosure of retribution income at the Regional Finance Agency of Depok City. Recognition of retribution income is recognized based on the Operational Report and Budget Realization Report, where the Operational Report uses the accrual basis while the Budget Realization Report uses a cash basis in accordance with Government Accounting Standards. Retribution income is recognized on an accrual basis because the Operational Report is related to other Financial Statements such as the Changes in Equity Report and Balance Sheet, while the retribution income in the Budget Realization Report is made to determine the achievement of the revenue budget that was made at the beginning of the reporting period. Thus, the recognition of retribution income at the Regional Finance Agency of Depok City is in accordance with applicable accounting regulations and standards.